Effect of Dietary Replacement of Maize with Finger Millet (Eleusine coracana) Grain on Production Performance and Egg Quality of White Leghorn Hens - Tadele , Yilkal; Negesse, Tegene; Amha, Negassi; Yadav, K.R. (International Journal of Poultry Science, 2017)
Objective: A study was conducted to evaluate the effect of replacing maize by finger millet as energy source on feed intake, body weight gain, egg production and quality parameters of white leghorn layers. Materials and Methods: One hundred and eighty chickens were randomly distributed in 5 treatments, each replicated three times with ten layers and two cockerels/replicate in CRD and kept on a deep litter system. The treatment rations were formulated to contain finger millet in place of maize at the rate of 0 (T1), 25 (T2), 50 (T3), 75 (T4) and 100% (T5). Birds were offered a weighed amount of feed and feed leftover was collected and weighed the next morning. Weight of chicks was taken at the beginning and end of the experiment. Egg production and egg quality parameters were also recorded. Results: Finger millet contained 9% crude protein (CP) and 3280 kcal kg–1 metabolizable energy (ME) on DM basis. Dry matter intake among T1, T2, T3, T4 and T5 (94, 91, 94, 95 and 90 g/hen/day, respectively) was not different (p>0.05). There were significant differences (p